Identidade e alteridade no Reino Suevo da Galícia à partir das obras de Martinho de Braga ( c.550-579) - Meggiolaro, Rafael Hygino (2012)
This is a dissertation on the conversion about the Suevic kingdom of Galicia in the sixth century and the alterities that are apparent in the documents produced at the time. The conversion is attributed to the action of a bishop and abbot named Martin of Braga who wrote letters, poems, translations, and the minutes of the two Councils of Braga. He devoted his life to the consolidation of Catholic orthodoxy in Galicia. The social position from which Martin discloses his writings was privileged, especially the large number of worshippers who gave it authority and representativeness. Thus, the scope of his writings reached the German aristocracy which constituted the civil power lay in the region for more than one hundred years. With the conversion of the King, Catholicism has experienced a strengthening process, recorded in changing the apparatus with the emergence of urban basilicas and monasteries. From this, the task of fighting religious otherness revealed that Christianity still found obstacles to the unit aspirated. So what you notice is the defense of Christian identity and the attempt to annul the alterities considered enemies of the faith.